Financial Performance Analysis Using Economic Value Added at PT. Blue Bird Tbk - Matruty, Dinatonia J.; Loppies, Lilian Sonya; Taliak, Dwi Yuni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze financial performance analysis using economic value added at PT Blue Bird Tbk. The type of research used are descriptive research and verificative research. The data used in this study is in the form of financial report data for 2016 2020 sourced from idx.co.id. Data is analyzed using descriptive statistical methods. The calculation results show that economic value added at PT Blue Bird Tbk for the 2016 to 2020 period fluctuates. Economic value-added value at PT Blue Bird Tbk for the 2016 to 2020 period is above 0 or positive (> 0), then there has been an economic added value in the company.